2012
DOI: 10.1063/1.3676276
|View full text |Cite
|
Sign up to set email alerts
|

Chemical sensors based on randomly stacked graphene flakes

Abstract: We demonstrate a simple fabrication method to produce randomly stacked graphene chemiresistors using surfactant-assisted exfoliation of graphite. We analyze the sensitivity of such chemiresistors as a function of vacuum filtration volume and temperature. At low vacuum filtration volumes (<∼5 mL) the sensors exhibit superior sensitivity towards target molecules compared to previously developed polycrystalline graphene, polycrystalline graphene microribbon, and carbon nanotube chemical sensors. Temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 21 publications
0
32
1
Order By: Relevance
“…It was shown that the sensitivity of an isolated GB is B300 times higher than that of a single graphene grain and much larger than that of polycrystalline graphene sensors. We have verified that the presence of local transport gaps in GBs together with the local accumulation of gas molecules plays a crucial role in the observed large chemical sensitivity of GBs, so the mechanism differs from the previously reported carrier density modulation in carbon-based sensors 6,7,[23][24][25][26][27][28] . The sensing mechanism is based on a marked closing or opening of local conduction channels through the GB by the adsorbed …”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…It was shown that the sensitivity of an isolated GB is B300 times higher than that of a single graphene grain and much larger than that of polycrystalline graphene sensors. We have verified that the presence of local transport gaps in GBs together with the local accumulation of gas molecules plays a crucial role in the observed large chemical sensitivity of GBs, so the mechanism differs from the previously reported carrier density modulation in carbon-based sensors 6,7,[23][24][25][26][27][28] . The sensing mechanism is based on a marked closing or opening of local conduction channels through the GB by the adsorbed …”
Section: Discussioncontrasting
confidence: 44%
“…T opological defects improve the sensitivity of carbon-based chemical sensors towards gas molecules due to an efficient physisorption and enhanced charge transfer process [1][2][3][4][5][6][7] . Since such defects are formed within a single-crystalline graphene lattice, they have a modest effect on the electronic properties of the device.…”
mentioning
confidence: 99%
“…53,54 It is found that the resistance does not depend on the temperature for the sample fabricated with annealing (NGr-NiO/IDE-Anneal), while the resistance varies significantly with temperature for the sample fabricated without annealing (NGr-NiO/IDE). The details of I-V curves for the non-annealed and annealed IDE samples are given in Figure S12 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 25 The dependence of the resistance on the temperature confirms the influence of the hopping-type transport on the conductivity of NGr-NiO/IDE.…”
Section: Methodsmentioning
confidence: 94%
“…54,55 The measured resistance logarithm is evaluated as a function of 1/T 1/4 in Figure 9. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 26 The basic drift-diffusion equation describing the charge-carrier flow (current density) in disordered organic semiconductors is given by:…”
Section: Methodsmentioning
confidence: 99%
“…Van der Waals and Casimir interactions are of primary importance in biological systems, and the dielectric properties of the cell membrane have been found to be crucial for the description of such forces [15,16].At the same time, graphene with its remarkable optical, electric, and mechanical properties, has allowed the development of new functional devices. A number of studies have proposed graphene-based devices such as field-effect transistors [17,18], sensors [19,20] and supercapacitors [21,22]. It has also been discovered that bacterial cell membranes can be damaged by sharp-corner graphene sheets [23,24].…”
Section: Introductionmentioning
confidence: 99%